Mulberry (Morus atropurpurea Roxb.) leaf protein hydrolysates ameliorate dextran sodium sulfate-induced colitis via integrated modulation of gut microbiota and immunity. (September 2021) - Sun, Chongzhen; Tang, Xin; Shao, Xin; Han, Duo; Zhang, Hua; Shan, Yangwei; Gooneratne, Ravi; Shi, Lei; Wu, Xiyang; Hosseininezhad, Marzieh
Graphical abstract: Highlights: Mulberry leaf protein hydrolysates (MLPH) efficiently alleviated DSS-induced colitis. Prevention and therapeutic intervention was more effective than therapeutic intervention. MLPH reversed microbiota dysbiosis and increased colonization of SCFA-producing genera. Lactobacillus and Desulfovibrio are the key bacteria in MLPH group. Dominant genera in MLPH group positively correlated with IBD prevention parameters. Abstract: The molecular action underlying peptide intervention before and after colitis induction is different. To investigate the alleviated effects of mulberry leaf protein hydrolysates (MLPH) on colitis and its potential mechanism, MLPH was administered to colitis mice. Results showed that MLPH efficiently alleviated the colitis, and the preventive and therapeutic (P&T) intervention was more effective than the therapeutic intervention alone. MLPH significantly decreased pro-inflammatory cytokines, improved histological damage, and increased SCFA contents. MLPH also reversed microbiota dysbiosis. The dominant genera in MLPH intervention group were significantly positively correlated with colitis prevention parameters ( p  < 0.01). The DSS group was the opposite. In addition, the dominant genera of MLPH intervention group showed a co-occurrence relationship with each other. Overall, MLPH could alleviate colitis by integrated modulation of gut microbiota and inflammation response. MLPH may be a promising dietary approach for sustaining gut health to lower the risk of developing colitis.